High trees increase sunflower seed predation by birds in an agricultural landscape of Israel - Schäckermann, Jessica; Weiss, Noam; von Wehrden, Henrik; Klein, Alexandra-Maria (Frontiers in Ecology and Evolution, 2014)
Natural habitats in agricultural landscapes promote agro-ecosystem services but little is known about negative effects (dis-services) derived by natural habitats such as crop seed predation. Birds are important seed predators and use high landscape structures to perch and hide. High trees in agricultural landscapes may therefore drive seed predation. We examined if the presence, the distance and the percentages of high trees (tree height >5 m) and the percentages of natural habitat surrounding sunflower fields, increased seed predation by birds in Israel. At the field scale, we assessed seed predation across a sample grid of an entire field. At the landscape scale, we assessed seed predation at the field margins and interiors of 20 sunflower fields. Seed predation was estimated as the percentage of removed seeds from sunflower heads. Distances of sample points to the closest high tree and percentage of natural habitat and of high trees in a 1km radius surrounding the fields were measured. We found that seed predation increased with decreasing distance to the closest high tree at the field and landscape scale. At the landscape scale, the percentage of high trees and natural habitat did not increase seed predation. Seed predation in the fields increased by 37 %, with a maximum seed predation of 92 %, when a high tree was available within zero to 50 m to the sunflower fields. If the closest high tree was further away, seed predation was less than 5 %. Sunflower seed predation by birds can be reduced, when avoiding sowing sunflowers within a radius of 50 m to high trees. Farmers should plan to grow crops, not sensitive to bird seed predation, closer to trees to eventually benefit from ecosystem services provided by birds, such as predation of pest insects, while avoiding these locations for growing crops sensitive to bird seed predation. Such management recommendations are directing towards sustainable agricultural landscapes.